Comprehensive Review of Health Informatics and Administrative Practices in Healthcare - Alharbi, Majed Sagi; Alotaibi, Ayad Mohsen; Alahmari, Mohammed Awadh Mohammed; Alrouji, Abdulrahman Zaid; Alolyaani, Mohammed Abdullah Mohammed; Alharbi, Khaled Saad Farhan; Albulayhid, Abdullah Mohammed Ibrahim; ALmutairi, Mohammed Jazaa Menwer; Alharbi, Turki Hamdi Duribis; Almutairi, Saud Jazaa Menwer (Journal of Ecohumanism, 2024)
Specifically, health informatics is an uphill profession responsible for changing the direction of healthcare systems to manage a massive amount of healthcare data. This paper explores the integration of health informatics with healthcare admission, focusing on the developments, trends, and issues encountered in the field. This paper aims to discuss healthcare organizations' key technologies, systems, and practices regarding clinical and administrative work approaches such as EHR, HIS, and telemedicine. This review looks at relevant studies and studies done in recent years and has highlighted how technology helps healthcare organizations deliver efficient, safe, and quality care. The paper also features recommendations for improving health informatics and other administrative practice outcomes, emphasizing future trends in healthcare technology.